Studies of Swelling Kinetics of Carboxymethyl Cellulose-g-PMAAm-co-PNIPAm Superabsorbent Hydrogels - Soleimani, Fatemeh; Sadeghi, Hossein; Shahsavari, Hadis; Soleimani, Arezou; Sadeghi, Fatemeh (Asian Journal of Chemistry, 2013)
In this paper, we have focused on study of swelling kinetics and salt-sensitivity behaviour of a superabsorbing hydrogel based on carboxymethylcellulose and N-isopropylacrylamide and methacrylamide in a homogeneous solution. The swelling kinetics of the hydrogels with various particle sizes was investigated as well. The swelling of the hydrogel showed a second order kinetics of swelling in water. In addition, swelling measurements of the synthesized hydrogels in various chloride salt solutions was measured. Results indicated that a swelling-loss with an increase in the ionic strength of the salt solutions.